Development of Basic Physics E-Module I Particle Dynamics Material Based on Kvisoft Flipbook Maker - Damayanti, Roza (Program Magister Teknologi Pendidikan Universitas Jambi, 2015)
This type of research is (research and development) with the ADDIE development model which includes analysis, design, development, implementation and evaluation. The subjects of this research were 2016 PGMIPA-U Physics Education students at Jambi University. The research instruments used were media expert validation questionnaires, material expert validation questionnaires and student perception questionnaires. The qualitative data analysis technique is carried out using descriptive analysis, while quantitative data is carried out using descriptive statistical analysis. The results of the questionnaire trial showed that there were 16 valid statements and one invalid statement. The reliability value obtained was 0.898 in the very high category. Furthermore, the results of student perception research obtained data covering 3 aspects, namely the object aspect 19.49 in the good category, for the sensory aspect it was 19.21 in the good category, while for the attention aspect it was 13.7 in the very good category. The average score for all student perception indicators is 52.61 in the very good category. Based on the results obtained in the research, it can be concluded that the development of the Basic Physics I e-module on particle dynamics based on Kvisoft flipbook maker is very suitable for use as a teaching material in the Basic Physics I particle dynamics course at Jambi University.